2003
DOI: 10.1128/jcm.41.7.3192-3197.2003
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying Collection of Corneal Specimens in Cases of Suspected Bacterial Keratitis

Abstract: Identification of the causative organisms in suspected bacterial keratitis traditionally involves collecting multiple corneal scrapes, which are plated directly onto different solid agar culture media. Difficulties have been reported with this practice, so the development of a simpler diagnostic method in suspected bacterial keratitis would be useful. It is unclear whether a single corneal scrape sent to the microbiology laboratory in a liquid transport culture medium (indirect method) is as reliable for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 24 publications
5
66
1
1
Order By: Relevance
“…If no laboratory-skilled assistant can be present at the time of sampling, basic microbiologic training should be given to the ophthalmologist, and fresh media should be provided as required. Data showing a rate of definitive diagnosis (70.4%) that is among the highest of those published (1,2,3) are the basis for this encouragement.…”
Section: Investigating Infectious Keratitismentioning
confidence: 98%
See 2 more Smart Citations
“…If no laboratory-skilled assistant can be present at the time of sampling, basic microbiologic training should be given to the ophthalmologist, and fresh media should be provided as required. Data showing a rate of definitive diagnosis (70.4%) that is among the highest of those published (1,2,3) are the basis for this encouragement.…”
Section: Investigating Infectious Keratitismentioning
confidence: 98%
“…070, 2003). Similarly to Kaye et al (2), Nicola et al found that 55% of patients had received an antibiotic treatment before being evaluated in our center, and this clearly affected the recovery of an etiologic agent (45% versus 80%, with and without previous treatment, respectively [P Ͻ 0.01]). Moreover, in some cases, the pathogens were detected in only one of the inoculated media, and it was not unusual that very few colonies (fewer than five) grew on agar plates.…”
Section: Investigating Infectious Keratitismentioning
confidence: 99%
See 1 more Smart Citation
“…Then samples were incubated at 37°C for 24 hours for propagation. 12,13 Isolation and identification of pathogenic bacteria After incubation, a loopful of each enriched culture was streaked on CLED agar and Nutrient agar plates were incubated at 37°C for 24 hours. Colonies with different morphological characters and Gram's characters were selected and inoculated on respective selective media viz.…”
Section: Enrichment Of Samplesmentioning
confidence: 99%
“…However, even if a specimen of the corneal infiltrate is obtained for microbiological investigation using traditional method, subsequent growth and identification of pathogens occurs only in average of 50.47% cases (Kratz et al 2006). The traditional method involves the use of multiple specimens scraping with direct inoculation onto enriched solid culture agar plates (Kaye et al 2003). Studies were conducted to study the suitability of other transport medium and commercially available broth culture medium to increase positive yields (Kratz et al 2006;Kaye et al 2003).…”
mentioning
confidence: 99%